Religious Populism in Mainstream Media between Indonesia and India - Kansong, Usman; Sunarwinadi, Ilya Revianti; Triputra, Pinckey (Jurnal The Messenger, 2022)
Introduction: The mainstream media used political and media logic on religious populism to reinforce ideological changes in contemporary society. This study investigated how media mediatize the 212 rally (aksi 212) and the 2017 Jakarta Governorial Election as religious populism cases. This study also compared how media in Indonesia and India delivered the content based on the majority identity.Methods: This study applied a qualitative approach. Detik.com, Metro TV, and Republika Daily were selected based on their delivery content platform and media ownership. The qualitative content analysis was applied to explore the concepts of political and media logic. Then, the results of Islamic populism in Indonesia were compared with Hindu populism in India.Findings: This study found that the three media mediatized aksi 212 and the 2017 Jakarta Governorial Election as religious populism by using direct interaction. Detik.com was applying media logic while Metro TV and Republika Daily performed political logic. In comparing religious populism between Indonesia and India, the finding confirmed that populism came from a major identity. The finding showed that economic motivation could be escalated in parallel with religious identity.    Originality: This study become a novelty since no previous studies investigate the different delivery content platforms and the media ownership including comparing the mediatization process between two countries. Previous studies focused on the media concentration based on media ownership, platform, media landscape, and media policy without a mediatization process and religious populism. The previous studies of the mediatization of religious populism were conducted in a single case.